2020
DOI: 10.1097/eja.0000000000001134
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of a low-dose esketamine versus an alfentanil adjunct to propofol sedation during endoscopic retrograde cholangiopancreatography

Abstract: BACKGROUND Endoscopic retrograde cholangiopancreatography (ERCP) is one of the most complex gastrointestinal endoscopic procedures. Currently, it is still unclear which sedation regimen best facilitates an ERCP. The N-methyl-d-aspartate receptor antagonist esketamine has anaesthetic, analgesic and sympathomimetic properties and is known to cause less cardiorespiratory depression than other sedatives. It could therefore be an ideal adjunct to propofol for deep sedation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
131
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 94 publications
(144 citation statements)
references
References 19 publications
8
131
1
4
Order By: Relevance
“…Esketamine, a N-methyl-D-aspartate receptor antagonist, has analgesic, anaesthetic and sympathomimetic properties. It is reported that esketamine cause less respiratory or cardiovascular depression than other sedatives due to an increase in sympathetic tone [12,32]. Jonkman K et al found that esketamine could counter opioid-induced respiratory depression [11].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Esketamine, a N-methyl-D-aspartate receptor antagonist, has analgesic, anaesthetic and sympathomimetic properties. It is reported that esketamine cause less respiratory or cardiovascular depression than other sedatives due to an increase in sympathetic tone [12,32]. Jonkman K et al found that esketamine could counter opioid-induced respiratory depression [11].…”
Section: Discussionmentioning
confidence: 99%
“…It is also reported that esketamine nasal spray could cause transient and asymptomatic blood pressure elevations [33]. Therefore, there has been growing interest in the use of esketamine as an ideal adjunct to propofol for procedural sedation and analgesia [12,34]. It was reported that the use of a combination of propofol and esketamine for procedural analgesia and sedation during MR-guided HIFU treatments of uterine fibroids is feasible and safe, with a short recovery time and a low risk of major adverse events [34].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations